OXYCARDIN EFFECTS ON HEMOSTASIS AND BLOOD RHEOLOGY IN PATIENTS WITH STABLE ANGINA - Sun Zhun Khuan; N. A. Volov; V. N. Soboleva; S. M. Otarova; V. A. Lusov (Российский кардиологический журнал)
The study assessed oxycardin effects on hemostasis and blood rheology in 82 patients with stable angina, Functional Class II-III. In all participants, main parameters of hemostasis, blood viscosity, and red blood cell aggregation and deformation were investigated. Oxycardin course resulted in significantly reduced platelet aggregation, without affecting plasma hemostasis. A reduction in blood viscosity (shift rate 20 s-1) and in platelet aggregation index was also observed. Oxycardin combination with long-term aspirin therapy resulted in further reduction of platelet functional activity. The results obtained confirm oxycardin anti-aggregant activity and its beneficial influence on blood rheology.